Impact of physical and biological processes on temporal variations of the ocean carbon sink in the mid-latitude North Atlantic (2002–2016). (January 2020) - Macovei, Vlad A.; Hartman, Susan E.; Schuster, Ute; Torres-Valdés, Sinhué; Moore, C. Mark; Sanders, Richard J.
Highlights: Annual mean seawater pCO2 has not increased between 2002 and 2016 at the PAP site. The winter-summer seasonality of seawater pCO2 has however increased with time. The study area was a carbon sink with increasing CO2 flux into the ocean. Redfieldian carbon consumption was observed during the spring blooms. Gas exchange, biological production and mixing explain most of the pCO2 variability. Abstract: The ocean is currently a significant net sink for anthropogenically remobilised CO2, taking up around 24% of global emissions. Numerical models predict a diversity of responses of the ocean carbon sink to increased atmospheric concentrations in a warmer world. Here, we tested the hypothesis that increased atmospheric forcing is causing a change in the ocean carbon sink using a high frequency observational dataset derived from underway p CO2 (carbon dioxide partial pressure) instruments on ships of opportunity (SOO) and a fixed-point mooring between 2002 and 2016. We calculated an average carbon flux of 0.013 Pg yr −1 into the ocean at the Porcupine Abyssal Plain (PAP) site, consistent with past estimates. In spite of the increase in atmospheric p CO2, monthly average seawater p CO2 did not show a statistically significant increasing trend, but a higher annual variability, likely due to the decreasing buffer capacity of the system. The increasing Δ pCO 2 led to an increasing trend in the estimated CO2 flux into the ocean of 0.19 ± 0.03 mmol m −2 day −1 per year across the entire 15 year time series, making the study area a stronger carbon sink. Seawater p CO2 variability is mostly influenced by temperature, alkalinity and dissolved inorganic carbon (DIC) changes, with 77% of the annual seawater p CO2 changes explained by these terms. DIC is in turn influenced by gas exchange and biological production. In an average year, the DIC drawdown by biological production, as determined from nitrate uptake, was higher than the DIC increase due to atmospheric CO2 dissolution into the surface ocean. This effect was enhanced in years with high nutrient input or shallow mixed layers. Using the rate of change of DIC and nitrate, we observed Redfieldian carbon consumption during the spring bloom at a C:N ratio of 6.2 ± 1.6. A comparison between SOO and PAP sustained observatory data revealed a strong agreement for p CO2 and DIC. This work demonstrates that the study area has continued to absorb atmospheric CO2 in recent years with this sink enhancing over time. Furthermore, the change in p CO2 per unit nitrate became larger as surface buffer capacity changed.